PERAN KINERJA PETUGAS HAJI DALAM PELAYANAN CALON JEMAAH DI EMBARKASI JAKARTA TAHUN 2019 - hamidullah mahmud (Jurnal Manajemen Dakwah, 2020)
The Jakarta Embarkation Dormitory is a temporary stopover for prospective pilgrims in the DKI Jakarta and Banten Provinces before leaving for the holy land. Various preparations for departure and supplies are carried out by involving all officers who help serve all the needs of the congregation so that good performance needs to be carried out because this is related to the welfare of the prospective congregation.This study aims to determine the role of Hajj officers' performance in the implementation of departure services which include one stop service in multipurpose building 2, consumption and catering services, availability of facilities and infrastructure, worship guidance services, health services, services for elderly congregations, high risk and special needs. , as well as security services at the Jakarta Embarkation during the 2019 Hajj season. This study uses a qualitative descriptive method in which the results of the data are obtained from observations, interviews, and documentation.From the results of the research that the authors found in a series of services carried out by hajj officers at the Jakarta Embarkation, the results of the performance of hajj officers were good and optimal, meaning that the entire series went as planned. Hajj officers perform their main duties and functions in accordance with operating standards in the seven functional divisions of the Hajj Organizing Committee. Keywords: Performance, Hajj Officer, Service.